Positive electrode precursor with core-shell structure as well as preparation method and application of positive electrode precursor
By adopting the positive front drive body of the nuclear shell structure, the special structure design of the kernel and the shell layer is used to solve the structural unstable structure and lithium nickel mixed row of the high -nickel content ternary lithium -ion battery. And extension of service life.
Patent Information
- Application Number
- CN202411497687.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing ternary lithium-ion battery positive electrode materials are prone to problems such as poor crystallinity, excessive internal stress, increased irreversible charge and discharge reactions, severe gas production, poor circulation performance, and poor stability under high nickel content, which affects the overall performance and use of the battery. life.
The positive front drive body of the nuclear shell structure is designed through the special structure of the kernel and the shell layer, reducing the sintering temperature, suppressing mixed lithium nickel rows, and improving monocrystalline and electrochemical properties.
A significant reduction of the sintering temperature of the positive pole material, suppressing the phenomenon of mixed lithium nickel row, improving the electrochemical properties and cycle stability of the battery, and extending the service life of the battery.
Smart Images

Figure CN119370915A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a positive electrode precursor with a core-shell structure and a preparation method and application thereof. Background Art
[0002] The cathode materials of ternary lithium-ion batteries have shown excellent comprehensive performance due to the combination of nickel's high energy density, cobalt's excellent electrochemical properties, and manganese's cost-effectiveness and safety. They have been rapidly developed and applied in recent years. In particular, in order to meet the requirements of long driving range of pure electric vehicles, the nickel content in ternary cathode materials is getting higher and higher. With the increase of nickel content, the spherical nickel-cobalt-manganese hydroxide synthesized by the traditional coprecipitation method is calcined into polycrystalline cathode materials. When used in batteries, they are prone to a series of disadvantages such as poor crystallinity, excessive internal stress, increased irreversible charge and discharge reactions, severe gas production, poor cycle performance, and poor stability, which affect the overall performance and service life of the battery.
[0003] The single crystal structure can effectively alleviate the structural instability problem of high-nickel ternary materials. Single crystal particles have a continuous crystal structure, few grain boundaries, few intracrystalline defects, and small lattice distortion, which allows lithium ions to diffuse quickly and evenly along the channels inside the crystal during the charge and discharge process, thereby reducing the occurrence of interface side reactions and irreversible changes in the crystal structure, and improving the cycle stability and safety of ternary materials. In addition, single crystal particles usually have better mechanical strength and thermal stability, which helps to resist the stress and thermal shock generated during the charge and discharge process, and reduce particle breakage and material degradation.
[0004] However, the conditions for preparing single-crystal positive electrode materials require higher calcination temperatures than those for polycrystalline materials, which will aggravate the mixing of lithium and nickel and is not conducive to obtaining excellent electrochemical performance.
[0005] Therefore, how to reduce the degree of lithium-nickel mixing in single crystal positive electrode materials and improve the electrochemical performance of single crystal positive electrode materials is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a core-shell structured positive electrode precursor and a preparation method and use thereof. The core-shell structured positive electrode precursor provided by the present invention has high tap density and low impurity content, and can significantly reduce the sintering temperature when preparing single-crystal positive electrode materials, thereby effectively inhibiting the lithium-nickel mixing phenomenon in the positive electrode material, avoiding the agglomeration of the positive electrode material particles, improving the single crystallinity of the positive electrode material, and improving the electrochemical performance of the battery.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a positive electrode precursor with a core-shell structure, which comprises a precursor core and a precursor shell layer from the inside to the outside; the porosity of the precursor core is greater than the porosity of the precursor shell layer, and the primary grains in the precursor shell layer are arranged and distributed in a direction along the radial direction of the precursor shell layer.
[0009] The core-shell structured positive electrode precursor provided by the present invention has a special radial structure in which the core of the precursor has high porosity and disordered primary grains, and the shell layer has low porosity and directional primary grains. The tap density is high, and the core is prone to shrinkage during solid-phase sintering, which causes the spherical secondary particles to break, further promoting the single crystalization of the positive electrode material. The primary grains of the shell layer are radially oriented, which is beneficial to the mass transfer process during sintering. The synergistic effect can significantly reduce the sintering temperature when preparing single-crystal positive electrode materials from the positive electrode precursor material, thereby effectively suppressing the lithium-nickel mixed arrangement phenomenon in the positive electrode material and improving the electrochemical performance of the battery. The structure in which the core is loose and the primary grains of the shell layer are radially oriented is beneficial to the removal of impurity ions such as sodium and sulfur during the washing process of post-treatment, further optimizing the quality of the precursor.
[0010] In the present invention, if the primary grains in the outer shell layer are still distributed in a disordered state, the mass transfer process during sintering cannot be effectively promoted, and the sintering temperature cannot be reduced to inhibit lithium-nickel intermixing; and if the porosity of the inner core is lower than the porosity of the outer shell layer, the inner core of the precursor will not be easily broken after sintering or a higher sintering temperature will be required, and a single crystal positive electrode material with good dispersion and low lithium-nickel intermixing cannot be obtained.
[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0012] Preferably, the median particle size D50 of the core-shell structured positive electrode precursor is 2 to 8 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm or 8 μm, etc., preferably 3.5 to 6 μm.
[0013] Preferably, the median particle size D50 of the precursor core is 1.5-3 μm, for example, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm or 3 μm, etc.
[0014] In a second aspect, the present invention provides a method for preparing a positive electrode precursor with a core-shell structure as described in the first aspect, the preparation method comprising the following steps:
[0015] Mixing a metal mixed salt solution, a precipitant solution and a complexing agent solution, and performing a first coprecipitation reaction under a first oxidizing atmosphere to obtain a precursor core;
[0016] After obtaining the precursor core, adding an additive solution under a second oxidizing atmosphere to carry out a second coprecipitation reaction to obtain the positive electrode precursor of the core-shell structure;
[0017] Wherein, the oxygen concentration in the first oxidizing atmosphere is greater than the oxygen concentration in the second oxidizing atmosphere.
[0018] The preparation method provided by the present invention first carries out a first coprecipitation reaction under a strong oxidizing atmosphere to refine the primary grains, and then carries out a second coprecipitation reaction with a synergistic additive under a weak oxidizing atmosphere to induce the primary grains to grow in a radially oriented arrangement, thereby obtaining a positive electrode precursor with a core-shell structure having a special radial structure in which the core of the precursor has a high porosity and disordered arrangement of the primary grains, and the outer shell has a low porosity and directional arrangement of the primary grains. The preparation method is simple to operate, does not require a complicated preparation process, and is suitable for large-scale production.
[0019] In the present invention, if additives are also added during the first co-precipitation reaction, an internally disordered and loose porous structure cannot be obtained, and the additives are easily wrapped inside the particles during the rapid agglomeration after nucleation and are difficult to remove; and if no additives are added during the second co-precipitation reaction, the primary grains of the shell cannot be promoted to form a directional arrangement structure; further, if the oxygen concentration in the first oxidizing atmosphere is less than the oxygen concentration in the second oxidizing atmosphere, the porosity of the precursor core will be lower than the porosity of the precursor shell, and a higher sintering temperature will be required to obtain a single crystal positive electrode material with better dispersion; that is, in the preparation method provided in the present application, the first oxidizing atmosphere, the second oxidizing atmosphere and the additives work together to obtain a positive electrode precursor material with a special structure.
[0020] Preferably, the metal element in the metal mixed salt solution includes nickel.
[0021] Preferably, the metal elements in the metal mixed salt solution further include M elements, and the M elements include transition metal elements.
[0022] The present invention does not specifically limit the specific material type of the M element, and the present invention is applicable to all transition metal elements that can be used as precursor materials in layered oxide positive electrodes; the M includes but is not limited to at least one of manganese, cobalt or aluminum.
[0023] Preferably, based on the total molar amount of all metal elements in the metal mixed salt solution as 100%, the molar amount of nickel accounts for 33% to 98%, for example, 33%, 35%, 38%, 40%, 43%, 45%, 48%, 50%, 53%, 55%, 58%, 60%, 63%, 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 93%, 95% or 98%, etc.
[0024] Preferably, the mixed gas in the first oxidizing atmosphere includes a first oxygen-containing gas and a first non-oxygen gas, and the volume ratio of the first oxygen-containing gas to the first non-oxygen gas is (0.3-3):1, for example, 0.3:1, 0.5:1, 0.8:1, 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1 or 3:1, etc.
[0025] Preferably, the mixed gas in the second oxidizing atmosphere includes a second oxygen-containing gas and a second non-oxygen gas, and the volume ratio of the second oxygen-containing gas to the second non-oxygen gas is (0.02-0.2):1, for example, 0.02:1, 0.05:1, 0.08:1, 0.13:1, 0.15:1, 0.18:1 or 0.3:1, etc.
[0026] It should be noted that the types of the first oxygen-containing gas and the second oxygen-containing gas in the present invention independently include but are not limited to air, oxygen or ozone, etc.; the first non-oxygen gas and the second non-oxygen gas include but are not limited to protective gas, and the protective atmosphere includes nitrogen or other inert gases, etc.
[0027] In the present invention, by further adjusting the volume ratio of the first oxygen-containing gas to the first non-oxygen gas to (0.3-3):1 and / or the volume ratio of the second oxygen-containing gas to the second non-oxygen gas to (0.02-0.2):1, the pore structure and distribution of the core and shell of the precursor can be better adjusted to achieve the optimal design of the precursor with a specific structure.
[0028] Preferably, the mass fraction of the additive in the additive solution is 0.1-10%, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, etc.
[0029] In the present invention, the mass fraction of the additive is controlled to 0.1-10%, which is more conducive to ensuring that substantially no impurities are introduced while also promoting the directional arrangement of the primary grains of the precursor shell, thereby improving the quality of the precursor.
[0030] Preferably, the additive includes any one of polyvinyl pyrrolidone, polyethylene glycol, tetramethylammonium hydroxide, hexadecyltrimethylammonium bromide or triethanolamine, or a combination of at least two thereof.
[0031] Preferably, the reaction temperatures of the first coprecipitation reaction and the second coprecipitation reaction are each independently 40-80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.
[0032] Preferably, the rotation speeds of the first coprecipitation reaction and the second coprecipitation reaction are each independently 300-800 rpm, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm or 800 rpm, etc.
[0033] Preferably, the pH values of the first coprecipitation reaction and the second coprecipitation reaction are independently 10-11, for example, 10, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9 or 11, etc.
[0034] Preferably, after the second coprecipitation reaction is completed, washing and drying are performed in sequence.
[0035] Preferably, the water content of the core-shell structured positive electrode precursor is ≤0.8wt%.
[0036] As a preferred technical solution, the preparation method comprises the following steps:
[0037] Mixing a metal mixed salt solution, a precipitant solution and a complexing agent solution, and performing a first coprecipitation reaction in a first oxidizing atmosphere of a mixed gas of a first oxygen-containing gas and a first non-oxygen gas, wherein the volume ratio of the first oxygen-containing gas to the first non-oxygen gas is (0.3-3):1, to obtain a precursor core;
[0038] After obtaining the precursor core, in a second oxidizing atmosphere of a mixture of a second oxygen-containing gas and a second non-oxygen gas, the volume ratio of the second oxygen-containing gas to the second non-oxygen gas is (0.02-0.2):1, and then an additive solution with a mass fraction of 0.1-10% of the additive is added to perform a second coprecipitation reaction to obtain the positive electrode precursor of the core-shell structure;
[0039] Among them, the metal elements in the metal mixed salt solution include nickel elements, and the metal elements in the metal mixed salt solution also include M elements, and the M elements include transition metal elements; taking the total molar amount of all metal elements in the metal mixed salt solution as 100%, the molar amount of nickel accounts for 33% to 98%.
[0040] It should be noted that, in the preparation method provided by the present invention, except for the above-mentioned characteristic limitations, the specific types of the preparation raw materials, other preparation parameters, etc. are all conventional technical solutions, and those skilled in the art can make adaptive selections and adjustments according to actual needs;
[0041] Optionally, the metal mixed salt solution, the precipitant solution and the complexing agent solution can be added to the reaction base solution in parallel, or can be directly reacted. When the reaction base solution is contained, the reaction base solution includes water, a precipitant and a complexing agent. The pH value of the reaction base solution is 11.3 to 13, such as 11.3, 11.5, 11.8, 12, 12.3, 12.5, 12.8 or 13, etc. The concentration of the complexing agent in the reaction base solution is 2 to 15 g / L, such as 2 g / L, 5 g / L, 10 g / L or 15 g / L, etc.;
[0042] Optionally, the reaction process includes an inevitable nucleation process in the first oxidizing atmosphere (during the nucleation process, the pH value can be adjusted to >11.3), and the nucleation process is when the particles are stably present and no new particles appear, but the nucleation process ends when the particles start to grow;
[0043] Optionally, the total concentration of metal ions in the metal mixed salt solution is 1 to 3 mol / L, such as 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, and the type of the salt includes at least one of sulfate, nitrate, chloride or acetate, etc.;
[0044] Optionally, the mass fraction of the precipitant solution is 20-40%, such as 20%, 25%, 30%, 35% or 40%, etc., and the precipitant includes but is not limited to at least one of sodium hydroxide, potassium hydroxide or sodium carbonate, etc.;
[0045] Optionally, the mass fraction of the complexing agent solution is 10-25%, such as 10%, 15%, 20% or 25%, etc., and the complexing agent includes but is not limited to ammonia water or citric acid, etc.;
[0046] Optionally, the washing process adopts conventional alkaline washing plus water washing, and the number of washing times is two or more to fully remove residual sodium sulfur impurities.
[0047] In a third aspect, the present invention provides a single crystal positive electrode material, which is obtained by mixing and sintering a core-shell structured positive electrode precursor as described in the first aspect or a core-shell structured positive electrode precursor prepared by the preparation method as described in the second aspect with a lithium source.
[0048] The single crystal positive electrode material provided by the present invention has a low degree of lithium-nickel mixing and excellent electrochemical performance.
[0049] Preferably, the sintering includes sequentially performing a first sintering, a second sintering and a third sintering.
[0050] Preferably, the sintering atmosphere of the sintering is an oxygen-containing atmosphere.
[0051] Preferably, the sintering temperature of the first sintering is 400-650°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C or 650°C.
[0052] Preferably, the first sintering holding time is 3 to 10 h, for example, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0053] Preferably, the sintering temperature of the second sintering is 880-1000°C, for example, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C or 1000°C.
[0054] Preferably, the holding time of the second sintering is 3 to 12 h, for example, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or 13 h, etc., preferably 5 to 8 h.
[0055] Preferably, the sintering temperature of the third sintering is 780-850°C, for example, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C or 850°C.
[0056] In the present invention, the temperature of the third sintering is lower than that of the second sintering, that is, the temperature is raised and then lowered for sintering. The purpose is to continue the growth of single crystal particles at a slightly lower third sintering temperature after the precursor particles are basically completely broken under the high temperature of the second sintering, thereby avoiding the aggravation of lithium-nickel mixing caused by being in an extremely high temperature environment for a long time.
[0057] Preferably, the holding time of the third sintering is 3 to 12 h, for example, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or 13 h, etc., preferably 5 to 8 h.
[0058] In the present invention, three-stage sintering is more conducive to obtaining a single crystal positive electrode material with a low degree of lithium-nickel mixing, good dispersion and crystal form; the first sintering process fully removes the moisture in the mixture and substances such as CO2 and H2O produced by the reaction to avoid the generation of micropores; the second sintering process allows the secondary spherical particles to be fully broken under high temperature to form single crystal primary particles with good dispersion, and the third sintering process is conducive to the development of the broken single crystal primary particles into a single crystal positive electrode material with a larger size and good crystal form.
[0059] Preferably, the heating rates of the first sintering and the second sintering are independently 1 to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc., preferably 2 to 5°C / min.
[0060] Preferably, the cooling rate of the third sintering is 1-10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc., preferably 2-5°C / min.
[0061] It should also be noted that the type of lithium source, the amount of lithium source added, and the mixing method of the lithium source and the core-shell structured positive electrode precursor in the present invention are all conventional technical solutions;
[0062] Optionally, the lithium source includes but is not limited to at least one of lithium hydroxide, lithium carbonate, lithium nitrate or lithium acetate;
[0063] Optionally, the ratio of the molar amount of lithium in the lithium source to the total molar amount of Me element in the core-shell structured positive electrode precursor (that is, all metal elements in the positive electrode precursor material) is (1.04-1.2):1, for example, 1.04:1, 1.05:1, 1.08:1, 1.1:1, 1.12:1, 1.15:1 or 1.2:1, etc., and further preferably (1.08-1.12):1;
[0064] Optionally, the mixing method may be dry mixing or wet mixing;
[0065] Those skilled in the art can adjust the above preparation process according to actual needs.
[0066] In a fourth aspect, the present invention further provides a battery, comprising the single crystal positive electrode material as described in the third aspect.
[0067] Due to space limitations and to avoid redundancy, the present invention does not list all point values within the above numerical range one by one, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] (1) The core-shell structured positive electrode precursor provided by the present invention has a special radial structure in which the core of the precursor has high porosity and disordered primary grains, and the shell layer has low porosity and directional primary grains. The tap density is high, and the core is prone to shrinkage during solid-phase sintering, which causes the spherical secondary particles to break, further promoting the single crystallization of the positive electrode material. The primary grains of the shell layer are directional in the radial direction, which is beneficial to the mass transfer process during sintering. The synergistic effect can significantly reduce the sintering temperature when preparing single-crystalline positive electrode materials from the positive electrode precursor material, thereby effectively inhibiting the lithium-nickel mixing phenomenon in the positive electrode material and improving the electrochemical performance of the battery. At the same time, it also avoids the agglomeration of particles during the preparation of the positive electrode material. The particles have high dispersion and high single crystallinity. The structure in which the core is loose and the primary grains of the shell layer are directional in the radial direction is beneficial to the removal of impurity ions such as sodium and sulfur during the post-treatment washing process, further optimizing the quality of the precursor.
[0070] (2) The preparation method provided by the present invention first performs a first coprecipitation reaction under a strong oxidizing atmosphere to refine the primary grains, and then performs a second coprecipitation reaction with a synergistic additive under a weak oxidizing atmosphere to induce the primary grains to grow in a radially oriented manner, thereby obtaining a positive electrode precursor material with a special radial structure in which the core of the precursor has a high porosity and disordered arrangement of the primary grains, and the outer shell has a low porosity and oriented arrangement of the primary grains. The preparation method is simple to operate, does not require a complicated preparation process, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 This is a SEM image of the cross section of the core-shell structured positive electrode precursor provided in Example 1.
[0072] Figure 2 This is the SEM image of the single crystal positive electrode material provided for Application Example 1.
[0073] Figure 3 This is a SEM image of the cross section of the core-shell structured positive electrode precursor provided in Comparative Example 1.
[0074] Figure 4 SEM image of the single crystal positive electrode material provided in Comparative Application Example 1.
[0075] Figure 5 This is the SEM image of the single crystal positive electrode material provided for comparative application example 2. DETAILED DESCRIPTION
[0076] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0077] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0078] In the description of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the present invention, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.
[0079] Example 1
[0080] This embodiment provides a core-shell structured positive electrode precursor, wherein the core-shell structured positive electrode precursor comprises a precursor core Ni 0.6 Co 0.2 Mn 0.2 (OH)2 and precursor shell layer Ni 0.6 Co 0.2 Mn 0.2 (OH)2; the porosity of the precursor core is greater than the porosity of the precursor shell layer, and the primary grains in the precursor shell layer are arranged and distributed in a direction along the radial direction of the precursor shell layer.
[0081] The preparation method of the core-shell structured cathode precursor is as follows:
[0082] Step S1: According to the molecular formula Ni 0.6 Co 0.2 Mn 0.2 (OH)2 is used to prepare a mixed metal sulfate solution of nickel, cobalt and manganese, with a total metal ion concentration of 2 mol / L; a sodium hydroxide solution with a mass fraction of 32% as a precipitant is prepared; an ammonia solution with a mass fraction of 16% as a complexing agent is prepared; an additive solution is prepared according to a mass ratio of triethanolamine as an additive: pure water = 5:95 to obtain an additive solution with a mass fraction of 5% of the additive; a reaction bottom solution with a pH of 12.0-12.3 and an ammonia concentration of 5-6 g / L is prepared with liquid alkali, concentrated ammonia water and 20 L of pure water;
[0083] Step S2: In a strong oxidizing atmosphere (first oxidizing atmosphere) in which the volume ratio of the first non-oxygen gas nitrogen to the second oxygen-containing gas air is 1:1, the prepared mixed metal sulfate solution, sodium hydroxide solution and ammonia solution are added to a 50L reactor containing the base liquid at a flow rate of 1.86L / h, 0.76L / h and 0.26L / h, respectively, at a speed of 380rpm to carry out a first coprecipitation reaction at 50°C; the pH of the nucleation stage is controlled at 12.0±0.1 and maintained for 4h, and then the feed flow rate of the alkali solution is gradually reduced to make the pH of the reaction system 10.6±0.2 to continue the first coprecipitation reaction. After D50 reaches 2μm, the first stage coprecipitation reaction is terminated to obtain a precursor core;
[0084] The reaction atmosphere was adjusted to a weak oxidizing atmosphere (second oxidizing atmosphere) with a volume ratio of the second non-oxygen gas nitrogen: the second oxygen-containing gas air of 1:0.08, and 1 L of the additive solution was slowly pumped in by a peristaltic pump, and the reaction system was maintained at pH = 10.6 ± 0.2 and an ammonia concentration of 5 to 6 g / L to carry out the second coprecipitation reaction until the particle size D50 reached 4 μm, and then the feeding was stopped to obtain Ni 0.6 Co 0.2 Mn 0.2 (OH)2 precursor slurry;
[0085] The slurry is allowed to stand and the supernatant is extracted, then transferred to a scrubber, and washed three times with a 3% by mass dilute sodium hydroxide solution and three times with water using hot pure water at 60°C. After solid-liquid separation, the slurry is transferred to an oven and dried at 120°C to obtain a spherical or quasi-spherical core-shell structured positive electrode precursor with a D50 of 4 μm.
[0086] Example 2
[0087] This embodiment provides a core-shell structured positive electrode precursor, wherein the core-shell structured positive electrode precursor comprises a precursor core Ni 0.6 Co 0.2 Mn 0.2 (OH)2 and precursor shell layer Ni 0.6 Co 0.2 Mn 0.2 (OH)2; the porosity of the precursor core is greater than the porosity of the precursor shell layer, and the primary grains in the precursor shell layer are arranged and distributed in a direction along the radial direction of the precursor shell layer.
[0088] The preparation method of the positive electrode precursor is as follows:
[0089] Step S1: According to the molecular formula Ni 0.6 Co 0.2 Mn 0.2(OH)2 is used to prepare a mixed metal sulfate solution of nickel, cobalt and manganese, with a total metal ion concentration of 1 mol / L; a sodium hydroxide solution with a mass fraction of 20% as a precipitant is prepared; an ammonia solution with a mass fraction of 10% as a complexing agent is prepared; an additive solution is prepared according to a mass ratio of additive triethanolamine: pure water = 10:90 to obtain an additive solution with a mass fraction of 10% of the additive; a reaction bottom solution with a pH of 12.0-12.3 and an ammonia concentration of 5-6 g / L is prepared with liquid alkali, concentrated ammonia water and 20 L of pure water;
[0090] Step S2: In a strong oxidizing atmosphere with a volume ratio of the first non-oxygen gas nitrogen: the second oxygen-containing gas air of 1:3, the prepared mixed metal sulfate solution, sodium hydroxide solution and ammonia solution are added to a 50L reactor containing the base liquid at a flow rate of 1.86L / h, 0.76L / h and 0.26L / h, respectively, in a uniform and parallel flow manner, and a first coprecipitation reaction is carried out at a speed of 380rpm at 50°C; the pH of the nucleation stage is controlled at 12.0±0.1 and maintained for 4h, and then the feed flow rate of the alkali solution is gradually reduced to make the pH of the reaction system = 10.6±0.2 to continue the first coprecipitation reaction. After D50 reaches 3μm, the first stage coprecipitation reaction is terminated to obtain a precursor core;
[0091] The reaction atmosphere was adjusted to a weak oxidizing atmosphere with a volume ratio of the second non-oxygen gas nitrogen: the second oxygen-containing gas air of 1:0.2, and 1 L of the additive solution was slowly pumped in by a peristaltic pump, and the reaction system was maintained at pH = 10.6 ± 0.2 and an ammonia concentration of 5 to 6 g / L to carry out the second coprecipitation reaction until the particle size D50 reached 6 μm, and then the feeding was stopped to obtain Ni 0.6 Co 0.2 Mn 0.2 (OH)2 precursor slurry;
[0092] The slurry was allowed to stand and the supernatant was extracted before being transferred to a scrubber, where it was washed three times with a 3% by mass dilute sodium hydroxide solution and three times with water using hot pure water at 60°C. After solid-liquid separation, it was transferred to an oven and dried at 120°C to obtain a spherical or quasi-spherical core-shell structured positive electrode precursor with a D50 of 6 μm.
[0093] Example 3
[0094] This embodiment provides a core-shell structured positive electrode precursor, wherein the core-shell structured positive electrode precursor comprises a precursor core Ni 0.6 Co 0.2 Mn 0.2 (OH)2 and precursor shell layer Ni 0.6 Co 0.2 Mn 0.2(OH)2; the porosity of the precursor core is greater than the porosity of the precursor shell layer, and the primary grains in the precursor shell layer are arranged and distributed in a direction along the radial direction of the precursor shell layer.
[0095] The preparation method of the positive electrode precursor is as follows:
[0096] Step S1: According to the molecular formula Ni 0.6 Co 0.2 Mn 0.2 (OH)2 was used to prepare a mixed metal sulfate solution of nickel, cobalt and manganese, with a total metal ion concentration of 2 mol / L; a sodium hydroxide solution with a mass fraction of 32% as a precipitant was prepared; an ammonia solution with a mass fraction of 16% as a complexing agent was prepared; an additive solution was prepared according to a mass ratio of triethanolamine as an additive: pure water = 1:99 to obtain an additive solution with a mass fraction of 1% of the additive; a reaction bottom solution with a pH of 11.5-11.8 and an ammonia concentration of 5-6 g / L was prepared with liquid alkali, concentrated ammonia water and 20 L of pure water;
[0097] Step S2: In a strong oxidizing atmosphere with a volume ratio of the first non-oxygen gas nitrogen to the second oxygen-containing gas air of 1:0.3, the prepared mixed metal sulfate solution, sodium hydroxide solution and ammonia solution are added to a 50L reactor containing the base liquid at a flow rate of 1.86L / h, 0.76L / h and 0.26L / h, respectively, in a uniform and parallel flow manner, and a first coprecipitation reaction is carried out at a speed of 300rpm at 40°C; the pH of the nucleation stage is controlled at 12.5±0.1 and maintained for 4h, and then the feed flow rate of the alkali solution is gradually reduced to make the pH of the reaction system = 10.3±0.2 to continue the first coprecipitation reaction. After D50 reaches 2μm, the first stage coprecipitation reaction is terminated to obtain a precursor core;
[0098] The reaction atmosphere was adjusted to a weak oxidizing atmosphere with a volume ratio of the second non-oxygen gas nitrogen: the second oxygen-containing gas air of 1:0.02, and 1 L of the additive solution was slowly pumped in by a peristaltic pump, and the reaction system was maintained at pH = 10.3 ± 0.2 and an ammonia concentration of 5 to 6 g / L to carry out the second coprecipitation reaction until the particle size D50 reached 4 μm, and then the feeding was stopped to obtain Ni 0.6 Co 0.2 Mn 0.2 (OH)2 precursor slurry;
[0099] The slurry is allowed to stand and the supernatant is extracted, then transferred to a scrubber, and washed three times with a 3% by mass dilute sodium hydroxide solution and three times with water using hot pure water at 60°C. After solid-liquid separation, the slurry is transferred to an oven and dried at 120°C to obtain a spherical or quasi-spherical core-shell structured positive electrode precursor with a D50 of 4 μm.
[0100] Example 4
[0101] The difference between this embodiment and embodiment 1 is that the chemical formula of the core-shell structure positive electrode precursor in this embodiment is Ni 0.8 Co 0.1 Mn 0.1 (OH)2.
[0102] In the preparation method, the nickel-cobalt-manganese mixed metal sulfate solution is prepared according to the molecular formula Ni 0.8 Co 0.1 Mn 0.1 (OH)2 preparation, and the additive is tetramethylammonium hydroxide.
[0103] The rest of the preparation methods and parameters were the same as those in Example 1.
[0104] Example 5
[0105] The difference between this embodiment and embodiment 1 is that in step S2 of this embodiment, the volume ratio of nitrogen to air in the first oxidizing atmosphere is 1:0.2.
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 6
[0108] The difference between this embodiment and embodiment 1 is that in step S2 of this embodiment, the volume ratio of nitrogen to air in the first oxidizing atmosphere is 1:3.5.
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Example 7
[0111] The difference between this embodiment and embodiment 1 is that in step S2 of this embodiment, the volume ratio of nitrogen to air in the second oxidizing atmosphere is 1:0.25.
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Example 8
[0114] The difference between this embodiment and embodiment 1 is that in step S1 of this embodiment, the mass fraction of the additive is 15%.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 1 is that in the preparation method provided in this comparative example, the entire coprecipitation reaction process is carried out under a nitrogen atmosphere, and no additive solution is added.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Comparative Example 2
[0120] The difference between this comparative example and Example 1 is that in the preparation method provided in this comparative example, no additive solution is added.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Comparative Example 3
[0123] The difference between this comparative example and Example 1 is that in the preparation method provided in this comparative example, the first coprecipitation reaction is carried out under the second oxidizing atmosphere; the second coprecipitation reaction is carried out under the first oxidizing atmosphere, that is, the preparation sequence of the oxidizing atmosphere is adjusted.
[0124] The rest of the preparation methods and parameters were the same as those in Example 1.
[0125] Comparative Example 4
[0126] The difference between this comparative example and Example 1 is that in the preparation method provided in this comparative example, the additive solution is added in the first coprecipitation reaction stage, but not in the second coprecipitation reaction stage.
[0127] The rest of the preparation methods and parameters were the same as those in Example 1.
[0128] Table 1 shows the results of the physical and chemical properties of the core-shell structured positive electrode precursors provided by Examples 1-8 and Comparative Examples 1-4.
[0129] Table 1
[0130]
[0131]
[0132] The core-shell structured positive electrode precursors provided by Examples 1-8 and Comparative Examples 1-4 were used to prepare single crystal positive electrode materials.
[0133] Application Example 1
[0134] This application example provides a single crystal positive electrode material, and the preparation method of the single crystal positive electrode material is as follows:
[0135] The core-shell structured positive electrode precursor provided in Example 1 and lithium carbonate powder were weighed and mixed evenly according to a molar ratio of Li / Me=1.10:1, and three-stage solid-phase sintering was sequentially performed in an oxygen atmosphere, namely, a first sintering, a second sintering and a third sintering;
[0136] The first sintering is to increase the temperature from room temperature to 500°C at a heating rate of 4°C / min and keep it warm for 6 hours, the second sintering is to increase the temperature from 500°C to 900°C at a heating rate of 3°C / min and keep it warm for 8 hours, and the third sintering is to cool the temperature from 900°C to 780°C at a cooling rate of 3°C / min and keep it warm for 8 hours. After the sintering is completed, the sample is naturally cooled to room temperature in the furnace, and the sample is crushed and passed through a 300-mesh sieve to obtain the single crystal positive electrode material.
[0137] Application Example 2-8
[0138] The difference between Application Examples 2-8 and Application Example 1 is that the core-shell structured positive electrode precursors provided in Examples 2-8 are used as the preparation raw materials.
[0139] The rest of the preparation methods and parameters are consistent with those in Application Example 1.
[0140] Application Example 9
[0141] The difference between this application example and application example 1 is that the sintering process of this application example does not include a third sintering process.
[0142] The rest of the preparation methods and parameters are consistent with those in Application Example 1.
[0143] Application Example 10
[0144] The difference between this application example and application example 1 is that the third sintering process of this application example is: heating from 900° C. to 1080° C. at a heating rate of 3° C. / min and keeping the temperature for 8 hours.
[0145] The rest of the preparation methods and parameters are consistent with those in Application Example 1.
[0146] Comparative Application Examples 1-4
[0147] The difference between comparative application examples 1-4 and application example 1 is that the core-shell structured positive electrode precursors provided by comparative examples 1-4 are respectively used as the preparation raw materials.
[0148] The rest of the preparation methods and parameters are consistent with those in Application Example 1.
[0149] Figure 1 The SEM image of the cross section of the core-shell structured positive electrode precursor provided in Example 1 is shown.
[0150] Figure 2 The SEM image of the single crystal positive electrode material provided in Application Example 1 is shown.
[0151] Figure 3 A SEM image of a cross section of a core-shell structured positive electrode precursor provided in Comparative Example 1 is shown.
[0152] Figure 4 The SEM image of the single crystal positive electrode material provided in Comparative Application Example 1 is shown.
[0153] Figure 5 The SEM image of the single crystal positive electrode material provided in Comparative Application Example 2 is shown.
[0154] contrast Figure 1 and Figure 3 It can be found that in Comparative Example 1, nitrogen protection is used throughout the co-precipitation reaction and no additives are added. The primary grains inside the obtained precursor particles have high density, only a small number of pores, and there is no orderly arrangement of the primary grains along the radial direction; while in Example 1, a strong oxidizing atmosphere is introduced during the inner core growth stage of the co-precipitation reaction, and a weak oxidizing atmosphere is introduced during the outer shell growth stage and additives are added, thereby obtaining a special radial structure with high internal porosity and disordered arrangement of primary grains, and low external porosity and directional arrangement of primary grains.
[0155] contrast Figure 2 , Figure 4 and Figure 5 It can be found that under the same sintering process, the positive electrode material prepared from the precursor obtained in Example 1 has more obvious single crystal characteristics and high dispersion of single crystal particles; the positive electrode material prepared from the precursor obtained in Comparative Example 1 is partially agglomerated single crystal-like particles with poor particle dispersion; the positive electrode material prepared from the precursor obtained in Comparative Example 2 still has partially agglomerated single crystal-like particles, and the particle dispersion is still poor, which cannot solve the problem of improving the single crystal degree of the positive electrode material.
[0156] The single crystal positive electrode materials provided in Application Examples 1-10 and Comparative Application Examples 1-4 are used to prepare lithium-ion batteries:
[0157] Preparation of positive electrode sheet: prepare positive electrode slurry according to the ratio of positive electrode material: SP: PVDF = 90:5:5, and obtain single crystal positive electrode slurry for use, wherein the slurry solid content is 60%; place aluminum foil on a coating machine, use a 150μm film applicator to place it on the aluminum foil, pour the single crystal slurry, start the equipment for coating, and obtain the electrode sheet after coating, place the electrode sheet in a 110°C oven for drying, and roll press to obtain the positive electrode sheet;
[0158] The positive electrode sheets provided in Application Examples 1-10 and Comparative Application Examples 1-4 were cut into discs with a diameter of 15 mm in a dry environment using a punch press. A metal lithium sheet was used as a counter electrode in a glove box. A ceglar composite membrane was selected as the isolation membrane. An electrolyte was added to assemble a button cell. The electrolyte was an organic solution obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of 30:50:20. The concentration of lithium salt (lithium hexafluorophosphate) in the electrolyte was 1.15 mol / L.
[0159] The performance tests of the button batteries provided in Examples 1-9 and Comparative Examples 1-2 were performed using the Wuhan Blue Electric CT2001A system:
[0160] (1) First discharge capacity: The voltage range is 2.8 to 4.25 V, and the charge and discharge rate is 0.2C. The charge and discharge test is performed to obtain the first discharge specific capacity at 0.2C;
[0161] (2) Rate performance: The voltage range is 2.8 to 4.25 V, the charge rate is 0.2C, and the discharge rate is 0.2C and 1C. The charge and discharge test is performed to obtain the discharge capacity ratio of 1C / 0.2C;
[0162] (3) Cycle performance: The voltage range is 2.8 to 4.25 V, and the charge and discharge rate is 1C. The charge and discharge test is performed to obtain the capacity retention rate after 100 cycles.
[0163] The test results of the above tests are shown in Table 2. Table 2 also shows the I of the single crystal positive electrode materials provided by Application Examples 1-10 and Comparative Application Examples 1-4. 003 / I 104 Ratio of:
[0164] Table 2
[0165]
[0166]
[0167] From Table 1-Table 2, we can get:
[0168] From the data results of Application Examples 1-4, it can be seen that the cathode precursor with a special core-shell structure provided by the present invention is conducive to the removal of impurity ions such as sodium and sulfur during the post-treatment washing process, further optimizing the quality of the precursor; it can also significantly reduce the sintering temperature when preparing a single crystal cathode material from the cathode precursor with a core-shell structure, thereby effectively inhibiting the lithium-nickel mixing phenomenon in the cathode material, and improving the capacity, rate and cycle performance of the battery;
[0169] From the data results of Application Examples 1 and Application Examples 5-7, it can be seen that in the process of preparing the positive electrode precursor material, by further adjusting the volume ratio of the first oxygen-containing gas and the first non-oxygen gas to (0.3-3):1 and / or the volume ratio of the second oxygen-containing gas and the second non-oxygen gas to (0.02-0.2):1, the pore structure and distribution of the precursor core and shell can be better adjusted, and the optimized design of the precursor with a specific structure can be achieved, thereby further improving the capacity, rate and cycle performance of the positive electrode material;
[0170] From the data results of Application Examples 1 and 8, it can be seen that the mass fraction of the additive is adjusted to 0.1-10%, which is more conducive to improving the structural stability of the precursor material and promoting the directional arrangement of the primary grains of the shell, thereby further improving the capacity, rate and cycle performance of the positive electrode material;
[0171] From the data results of Application Examples 1 and Application Examples 9-10, it can be seen that in the process of preparing the positive electrode material from the positive electrode precursor material, three-stage sintering is performed, and the sintering process is regulated to be a heating-heating-cooling law, which is more conducive to the single crystallization of the positive electrode material, and further realizes the improvement of the capacity, rate and cycle performance of the positive electrode material;
[0172] From the data results of Application Example 1 and Comparative Application Examples 1-4, it can be seen that in the present invention, the order of adding additives and the regulation of the oxygen concentration in the first oxidizing atmosphere and the second oxidizing atmosphere are indispensable. If any one of the conditions is missing, the positive electrode precursor with a special core-shell structure in the present invention cannot be obtained, and it is also impossible to reduce the impurity content in the positive electrode precursor and improve the degree of single crystallization of the subsequent positive electrode material, which leads to a significant reduction in the capacity, rate and cycle performance of the positive electrode material.
[0173] In summary, the core-shell structured positive electrode precursor provided by the present invention has a special radial structure in which the porosity in the core of the precursor is high and the primary grains are randomly arranged, and the porosity in the outer shell is low and the primary grains are oriented. It has a high tap density, and the inner core is prone to shrinkage during solid-phase sintering, which causes the spherical secondary particles to break, further promoting the single crystalization of the positive electrode material, and the primary grains of the outer shell are radially oriented, which is beneficial to the mass transfer process during sintering. The synergistic effect can significantly reduce the sintering temperature when preparing single-crystalline positive electrode materials from the core-shell structured positive electrode precursor, thereby effectively inhibiting the lithium-nickel mixing phenomenon in the positive electrode material and improving the electrochemical performance of the battery; and the structure in which the inner core is loose and the primary grains of the outer shell are radially oriented is beneficial to the removal of impurity ions such as sodium and sulfur during the post-treatment washing process, further optimizing the quality of the precursor.
[0174] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A core-shell structured cathode precursor, characterized in that: The core-shell structured positive electrode precursor includes a precursor core and a precursor shell layer from the inside to the outside; the porosity of the precursor core is greater than the porosity of the precursor shell layer, and the primary grains in the precursor shell layer are arranged and distributed in a direction along the radial direction of the precursor shell layer.
2. The core-shell structured cathode precursor according to claim 1, characterized in that: The core-shell structured positive electrode precursor has a median particle size D50 of 2 to 8 μm, preferably 3.5 to 6 μm; Preferably, the median particle size D50 of the precursor core is 1.5-3 μm.
3. A method for preparing a core-shell structured cathode precursor as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: Adding a metal mixed salt solution, a precipitant solution and a complexing agent solution in parallel, and performing a first coprecipitation reaction under a first oxidizing atmosphere to obtain a precursor core; After obtaining the precursor core, adding an additive solution under a second oxidizing atmosphere to carry out a second coprecipitation reaction to obtain the positive electrode precursor of the core-shell structure; Wherein, the oxygen concentration in the first oxidizing atmosphere is greater than the oxygen concentration in the second oxidizing atmosphere.
4. The preparation method according to claim 3, characterized in that: The metal elements in the metal mixed salt solution include nickel elements; Preferably, the metal element in the metal mixed salt solution further includes an M element, and the M element includes a transition metal element; Preferably, the molar amount of nickel accounts for 33% to 98% based on the total molar amount of all metal elements in the metal mixed salt solution as 100%; Preferably, the mixed gas in the first oxidizing atmosphere comprises a first oxygen-containing gas and a first non-oxygen gas, and the volume ratio of the first oxygen-containing gas to the first non-oxygen gas is (0.3-3):1; Preferably, the mixed gas in the second oxidizing atmosphere comprises a second oxygen-containing gas and a second non-oxygen gas, and the volume ratio of the second oxygen-containing gas to the second non-oxygen gas is (0.02-0.2):1; Preferably, the mass fraction of the additive in the additive solution is 0.1 to 10%; Preferably, the additive includes any one of polyvinyl pyrrolidone, polyethylene glycol, tetramethylammonium hydroxide, hexadecyltrimethylammonium bromide or triethanolamine, or a combination of at least two thereof.
5. The preparation method according to claim 3 or 4, characterized in that: The reaction temperatures of the first coprecipitation reaction and the second coprecipitation reaction are each independently 40 to 80° C.; Preferably, the rotation speeds of the first coprecipitation reaction and the second coprecipitation reaction are independently 300 to 800 rpm; Preferably, the pH values of the first coprecipitation reaction and the second coprecipitation reaction are independently 10 to 11; Preferably, after the second coprecipitation reaction is completed, washing and drying are performed in sequence; Preferably, the water content of the core-shell structured positive electrode precursor is ≤0.8wt%.
6. The preparation method according to claim 3, characterized in that: The preparation method comprises the following steps: Adding a metal mixed salt solution, a precipitant solution and a complexing agent solution in parallel, performing a first coprecipitation reaction in a first oxidizing atmosphere of a mixed gas of a first oxygen-containing gas and a first non-oxygen gas, wherein the volume ratio of the first oxygen-containing gas to the first non-oxygen gas is (0.3-3):1, to obtain a precursor core; After obtaining the precursor core, in a second oxidizing atmosphere of a mixture of a second oxygen-containing gas and a second non-oxygen gas, the volume ratio of the second oxygen-containing gas to the second non-oxygen gas is (0.02-0.2):1, and then an additive solution with a mass fraction of 0.1-10% of the additive is added to perform a second coprecipitation reaction to obtain the positive electrode precursor of the core-shell structure; Among them, the metal elements in the metal mixed salt solution include nickel elements, and the metal elements in the metal mixed salt solution also include M elements, and the M elements include transition metal elements; taking the total molar amount of all metal elements in the metal mixed salt solution as 100%, the molar amount of nickel accounts for 33% to 98%.
7. A single crystal positive electrode material, characterized in that: The single crystal positive electrode material is obtained by mixing and sintering a positive electrode precursor with a core-shell structure as described in claim 1 or 2 or a positive electrode precursor with a core-shell structure prepared by the preparation method according to any one of claims 3 to 6 with a lithium source.
8. The single crystal positive electrode material according to claim 7, characterized in that: The sintering includes sequentially performing a first sintering, a second sintering and a third sintering; Preferably, the sintering atmosphere of the sintering is an oxygen-containing atmosphere.
9. The single crystal positive electrode material according to claim 8, characterized in that: The sintering temperature of the first sintering is 400-650° C., and the holding time of the first sintering is 3-10 hours; Preferably, the sintering temperature of the second sintering is 880-1000° C., and the holding time of the second sintering is 3-12 hours, preferably 5-8 hours; Preferably, the sintering temperature of the third sintering is 780-850° C., and the holding time of the third sintering is 3-12 hours, preferably 5-8 hours; Preferably, the heating rates of the first sintering and the second sintering are independently 1 to 10° C. / min, preferably 2 to 5° C. / min.
10. A battery, characterized in that: The battery comprises the single crystal positive electrode material as described in any one of claims 7 to 9.
Citation Information
Patent Citations
Nickel-cobalt-manganese hydroxide precursor and preparation method thereof
CN108306011A
Lithium ion battery positive electrode material precursor and preparation method and application thereof, lithium ion battery positive electrode material and preparation method and application thereof
CN115043440A
Ternary precursor material, ternary positive electrode material, preparation method of ternary precursor material and preparation method of ternary positive electrode material, and lithium ion battery
CN115231625A
Cobalt-free positive electrode material with porous core-shell structure and preparation method of cobalt-free positive electrode material
CN117558904A
Core-shell structure precursor and preparation method and application thereof
CN118598211A
Cited By
Core-shell structured positive electrode precursor, preparation method therefor and use thereof
WO2026086098A1